ARTIFICIAL INTELLIGENCE AS A SUPPORT FOR INDEPENDENT LIVING OF PEOPLE WITH DISABILITIES - Otašević, Jadranka R; Jovanovska, Mira (Serbian political thought, 2025)
Improving the quality of life and independence of people with disabilities is a challenge in the fields of social policy, technology, and law. The paper explores the application of artificial intelligence (AI) as a means of supporting independent living for this population, with a special focus on the possibilities of digital work and entrepreneurship. The theoretical framework of the paper is based on the functional and social model of disability and on the concept of inclusion and human rights. The relevant scientific literature, reports of international organizations (WHO, UNICEF, UN), as well as case studies and pilot projects in the field of digital support were analyzed. The results indicate that AI solutions significantly improve mobility, communication, access to information, and user confidence, but that their application is often limited by the lack of financial accessibility, appropriate policies, and active involvement of people with disabilities themselves in the process of creating AI support. Special attention is dedicated to employment challenges, where digital work is recognized as a potential solution, but is underutilized in our society. The need for accessible, ethical, and inclusive AI solutions is emphasized, as well as for the development of digital competencies in people with disabilities in order to achieve greater social and economic integration.
Keywords: people with disabilities; artificial intelligence; quality of life; inclusion; employment